Informal economy and graduate unemployment - Hadhek, Zouhaier; Hedhli, Mayssa (Technium Social Sciences Journal, 2025)
The informal economy unfortunately is still without a clear and precise definition indeed, it represents a contradictory reflection of advantages and disadvantages. The phenomenon of informality emerges when the formal sector becomes unable to absorb the new entrants to the labor market. Graduate unemployment also seems to be a global issue today that arises in North African countries and in Tunisia in particular. Our empirical work, which explores the relationship between graduate unemployment and the informal economy in Tunisia, rejects the hypothesis of the existence of a causal effect between these two variables. However, the increase in informality remains dependent on economic institutional variables (the degree of Tunisia’s economic freedom), political institutional variables such as political stability and government efficiency, and especially on public investment with the aim of improving the economy.